Effect of bran addition ratioon rheological properties of whole wheat flour - HAO Jian-yu; WANG Min; CAO Yong; MA Xiao-fei; LI Xiao-li; JIANG Lan-fang; HUO Wei-guang; JI Hu-tai (Liang you shipin ke-ji, 2019)
The effect of bran on rheological property of wheat flour was researched. The national trial strong gluten variety Jinmai 92 was used as raw material to grind flour.The bran addition were 5%, 10%, 15%, 20%, 25% and 30% with pure flour as negative control group and pure bran as positive control group.The rheological properties were determined by electronic farinograph, electronic extensograph and automatic bubblerin accordance with GB/T 14614-2006, GB/T 14615-2006 and GB/T 14614.4-2005. The results showed thatalong with the bran addition changed from 30% to 5%, the sedimentation value, farinograph stabilizing time and extensograph energy increased gradually, the maximum bubble pressure and Dmax gradually decreased, and blowing curve length, bubble inflation index and bubble deformation energy decreased at first then upward, the ratio of stretch ratio and bubble curve increased first and then decreased. As the bran addition was 5%~25%, the dough strength hreached the level of medium or moderately strong which can be used to make noodles or steamed bread.